2018
DOI: 10.1016/j.cmet.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Molecular Responses Differ between Gastric Bypass and Dieting but Are Conserved Across Species

Abstract: The effectiveness of Roux-en-Y gastric bypass (RYGB) against obesity and its comorbidities has generated excitement about developing new, less invasive treatments that use the same molecular mechanisms. Although controversial, RYGB-induced improvement of metabolic function may not depend entirely upon weight loss. To elucidate the differences between RYGB and dieting, we studied several individual organ molecular responses and generated an integrative, interorgan view of organismal physiology. We also compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 60 publications
2
46
1
Order By: Relevance
“…In our pilot study, the length of BP limb and AL limb were first set to be 6 cm each [13] which lead to death within 5 weeks due to malnutrition. Thus in this study we shorten the length of both limb to be 4cm each, which resulted in 36±3.7% average body weight loss without death from malnutrition, as comparable to other report [14]. Although creating a small gastric pouch with volume of 30ml (using a balloon gastric tube for measurement) is a standard step of RYGB in human [15], it is debatable to use such gastric pouch on mouse model [10,13,16].…”
Section: Discussionsupporting
confidence: 70%
“…In our pilot study, the length of BP limb and AL limb were first set to be 6 cm each [13] which lead to death within 5 weeks due to malnutrition. Thus in this study we shorten the length of both limb to be 4cm each, which resulted in 36±3.7% average body weight loss without death from malnutrition, as comparable to other report [14]. Although creating a small gastric pouch with volume of 30ml (using a balloon gastric tube for measurement) is a standard step of RYGB in human [15], it is debatable to use such gastric pouch on mouse model [10,13,16].…”
Section: Discussionsupporting
confidence: 70%
“…To date, most murine studies of SG have utilized a diet-induced model of obesity (DIO) or a genetically obese model, combined with sham pair-feeding, in an attempt to recapitulate and study SG physiology. [9,11,14,15,[39][40][41] While mice in these studies become obese and have hyperglycemia similar to the target patient population, investigations are limited by differences in food intake via pair-feeding and/or differences in body weight between the surgical intervention and sham groups. Furthermore, in most experiments, pair feeding induces weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a comprehensive tissue-wide translational study, Ben-Zvi et al (91) demonstrated using RNAsequencing that Ucp1 and Cidea mRNA expressions are higher in the inguinal WAT of RYGB-operated high-fat diet-induced obese male C57BL/6 mice compared to BWM sham-operated mice, as was UCP1 protein expression determined by representative immunohistochemistry. Importantly, this was complemented with indirect calorimetry measurements which confirmed higher energy expenditure in RYGB-operated mice compared to BWM sham-operated mice (91). While the underlying causal mechanisms for enhanced BeAT thermogenesis after RYGB compared to chronic caloric restriction-induced weight loss were not established in this particular study, mRNA expression of the anti-inflammatory cytokine interleukin-33 (Il33) was markedly increased in the inguinal WAT of RYGB-operated mice (91).…”
Section: Rygb and Bat/beat Thermogenesismentioning
confidence: 74%